IMPLEMENTATION OF CONTEXTUAL LEARNING STRATEGY IN THE QURAN HADITH IN THE PRIVATE MADRASAH TSANAWIYAH AL WASHLIYAH MEDAN KRIO SUNGGAL - Muhammad Habib Nasution, Syamsu Nahar, Edi Saputra (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: The purpose of this study is 1) To analyze the contextual strategy planning in learning theQur’anic Hadith in Private MTs Kec. Sunggal, 2) To analyze the implementation/application of contextuallearning strategies of the Qur’anic Hadith in Private MTs Kec. Sunggal, 3) To analyze the evaluation of thecontextual learning strategies of the Qur’an in the Private MTs Kec. Sunggal. With a qualitative researchmethodology using field research. Data collection techniques in the form of observation, interviews, anddocumentation. The findings of this study are 1) Contextual strategy planning in learning the Koran ofHadith at MTs Al Washliyah Medan Krio done through the stages of making the Learning ImplementationPlan (RPP) by the applicable curriculum. So that nothing comes out of the material that will discuss in thestudy of the Koran of Hadith. Furthermore, after the lesson plan is made and collected with the viceprincipaland the curriculum area is gathered in a teacher meeting to receive input from other teacherswho teach the same subjects or from other teachers with different subjects so that what is planned can beadjusted to the attitude students in class to further be carried out in learning, 2) Implementation of contextualstrategies in learning the Koran of Hadith in MTs Al Washliyah Medan Krio is to use appropriatelearning methods such as using illustrations and examples in learning that are appropriate to daily life, thento perpetuate their memories are related to the Qur’an and Hadith, the teacher gives memorization assignmentsto students and the teacher of the Qur’an Hadith always displays a simple profile so that it can be anexample for students, and 3) Evaluation of contextual strategies in learning the Qur’anic Hadith at MTs AlWashliyah Medan Krio is ah by conducting competency tests contained in the student worksheet (LKS),and evaluating the memorization of students with a memorized memorizing system and conducting routinetests including daily tests, midterm tests, and semester tests.Keywords: Contextual Learning Strategy, Quran Hadith, Al Washliyah